OPTIMISASI PROSES PENDINGINAN PUREE PADA INDUSTRI KECIL MENENGAH PENGOLAHAN BUAH - Hermawan; Fitria Dewi Sulistyono; Adriana Sari Aryani; Legis Tsaniyah (Journal of Innovation Research and Knowledge, 2022)
Small and medium scale (SME’s) puree processing industries generally do not yet have aseptic packaging technology, so they choose the hot filing packaging method. Hot purees that have been packaged in plastic bags must be cooled immediately to maintain the quality and nutritional value. In the 1000 kg puree production batch, the heat that must be discharged through the cooling process is 44,582.91 Kcal. The cooling process is transferring heat from the puree product to the cooling water media. The cooling process in the cooling tub is balanced by the time of pasteurization which is 10 minutes, so there is no bottleneck in the production system. The optimal heat transfer rate is 4,481.64 Kcal / minute to cooling water with a volume of at least 5.38 m3 for each ton of production batch. An optimal cooling time of 10 minutes can be achieved if the cooling bath is designed with a dimension of 8.4 meters long, 1.6 meters wide and 0.5 meters high. In this optimal condition, the cooling water in the tub is driven by the pump in the direction of the product flow at a 1.66 liter / second discharge